Environmental and Socioeconomic Impact Analysis of Quarry Operations in General Santos City on its Host Communities - Ngilay, Jama Nardzmah; Flores, Leonard (Journal of Interdisciplinary Perspectives, 2024)
Several international policies have been formulated to address the environmental and social impacts of the quarrying industry. However, this multifaceted issue persists, particularly in the Buayan River System in General Santos City. This study examined the environmental and socioeconomic repercussions of quarry operations in General Santos City, focusing on 14 commercial sand and gravel quarries along the Buayan River system. A mixed-methods approach was employed, collecting quantitative data through structured questionnaires, direct observations, and secondary data analysis, and incorporating qualitative insights from key informant interviews. Stakeholders within a 500-meter radius of the quarries were sampled using Quantum Geographic Information System (QGIS) to ensure representation. The findings revealed significant environmental impacts, including increased dust levels, soil erosion, and changes in water quality, which have adversely affected the local ecosystem and residents' health. The socioeconomic effects were mixed: while quarrying created jobs and improved infrastructure, it also showed deficiencies in community engagement and training programs. Regulatory analysis identified strengths in collaboration but highlighted weaknesses in enforcement, fee systems, and monitoring. The results indicated that although quarrying provides economic benefits, enhanced regulatory enforcement and sustainable practices are imperative to mitigate associated costs. Recommendations include strengthening enforcement, improving community engagement, updating fee structures, and implementing sustainable quarrying practices in General Santos City. By incorporating these recommendations, General Santos City can ensure the quarrying industry operates responsibly, balancing economic benefits with environmental and social well-being.